THE EFFECT OF TURN-TAKING READING ACTIVITY ON STUDENTS’ INTEREST IN ENGLISH LITERACY - Utary Rustam; Ernawati Ernawati (Al-Irsyad: Journal of Education Science, 2024)
This study examined the effectiveness of a literacy-based activity, namely the turn-taking reading activity to enhance students’ interest in reading and writing in English. A comparative research design was employed to compare students who participated in the activity with those who did not. Data were collected through a questionnaire consisting of 20 items measuring students’ interest in English reading and writing. The data were analyzed using a t-test to determine whether a significant difference existed between the two groups. The findings revealed that the turn-taking reading activity significantly influenced students’ interest in reading and writing English. Students in the turn-taking reading activity group demonstrated high levels of interest in both reading and writing (Reading = 34, Writing =34). In contrast, students in the non-turn-taking reading activity group showed moderate interest (Reading = 29, Writing = 27). Overall, the results indicate that the turn-taking reading activity is an effective strategy for increasing students’ interest in English literacy skills.